2020
DOI: 10.1175/jcli-d-19-0337.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Abnormally Enhanced MJO over the Western Pacific in the Formation and Subseasonal Predictability of the Record-Breaking Northeast Asian Heatwave in the Summer of 2018

Abstract: In the summer of 2018, Northeast Asia experienced a heatwave event that broke the existing high-temperature records in several locations in Japan, the Korean Peninsula, and northeastern China. At the same time, an unusually strong Madden–Julian oscillation (MJO) was observed to stay over the western Pacific warm pool. Based on reanalysis diagnosis, numerical experiments, and assessments of real-time forecast data from two subseasonal-to-seasonal (S2S) models, we discovered the importance of the western Pacific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…In the southeastern part of Australia, Parker et al (2014) showed that warm conditions are significantly associated with the phases 3-6 of the MJO. More recently, the summer 2018 long lasting heatwave over Northeast Asia was found by Hsu et al (2020) to have been favoured by an unusually strong MJO over the western Pacific warm pool.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…In the southeastern part of Australia, Parker et al (2014) showed that warm conditions are significantly associated with the phases 3-6 of the MJO. More recently, the summer 2018 long lasting heatwave over Northeast Asia was found by Hsu et al (2020) to have been favoured by an unusually strong MJO over the western Pacific warm pool.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…In our study, air-sea coupling has a similar effect on the simulated BSISO under different ocean background states, suggesting that the role of coupling may largely depend on the phase relationship between the convection and SST anomalies. Compared to daily coupling frequency between the atmosphere and ocean components of CGCMs, improved fidelity for the BSISO simulation is shown in CGCMs with sub-daily coupling frequency (Woolnough et al, 2007;Klingaman et al, 2011;Hu et al, 2015). In our study, the model ocean tends to respond quickly to the atmospheric convection, which may be associated with the sensitive mixed layer depth due to the absent ocean dynamics in KPP.…”
Section: Discussionmentioning
confidence: 70%
“…Superimposed on the large‐scale SST warming in the IO, an exceptionally persistent quasistationary MJO activity was observed during June–July 2020, very different from the eastward‐propagating features seen typically for MJO events. Tropical MJO‐associated convection activity has been long recognized as an important factor contributing to extreme temperature and rainfall anomalies over East Asia (e.g., Y. Chen & Zhai, 2017; Hong & Li, 2009; Hsu et al., 2020). During 2020, the MJO remained in Phases 1–3 (the tropical IO) throughout June–July with 59 active days during these 2 months (Figure 4a), far beyond the climatology (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%